New Idea for National Park Zoning System: a Synthesis between Biodiversity Conservation and Customary Community's Tradition - Nandi Kosmaryandi; Sambas Basuni; Lilik Budi Prasetyo; Soeryo Adiwibowo (Institut Pertanian Bogor (IPB University), 2012)
The establishment of national park in customary region had aroused conflic since it had not incorporate traditional management system in its management system. The objectives of this research is to develop such policies for national park zonation that amalgamating the national-global interests for conservation on the one side and the customary community interests on the other side. Result shows that adaptation was needed toward the prevailing science-based ecologically-oriented regulation on zoning plan, so it would incorporate the community's custom in order to achieve effective management of national park. Appropriate and applicable zoning can be achieved through implementation of management mindset with customary people livelihood perspectives, zone establishment which give priority to the achievement of national park functions rather than the fulfillment of zone requirements, and adaptation of zone formation and criteria toward traditional land use as efforts to accommodate the interest of biodiversity conservation and customary people livelihood.